Possible Use in Soil Bioremediation of the Bacterial Strain Bacillus Sphaericus NM-1 Capable of Simultaneously Degrading Promethrin and Acetochlor - Yue Cheng; Qian Fu; Junjia Xu; Xinhua Niu; Lin Liu; Jiaqi Wang; Jingwen Quan; Qingyue Yu; Baoyan Chi; Haitao Li; Rongmei Liu (Microorganisms)
Prometryn and acetochlor are herbicides used to control weeds in farmlands and other areas. They enter the soil through direct application, residual accumulation in crops, and atmospheric deposition. The pollution of their residues in the environment has attracted people’s attention. Bioremediation is one of the main methods to solve such problems. In this study, the effects of prometryn and acetochlor-degrading strain NM-1 on soil enzymes, soil microbial communities, and physiological indexes of soybean seedlings during soil remediation were studied, and the relationship between them was discussed. The results showed that 81.54% of prometryn (50 mg·L−1) and 89.47% of acetochlor (50 mg·L−1) were degraded within 15 days after NM-1 inoculation in soil. NM-1 positively affected soil enzyme activities and soil microbial communities, and the abundance of beneficial bacteria in soil increased. More importantly, the inoculation of strain NM-1 under prometryn and acetochlor stress significantly increased plant height, root length, root volume, water content, chlorophyll concentration, and root activity of soybean. The results of these studies showed that the NM-1 strain showed significant potential in bioremediation in order to provide technical support for solving the problem of prometryn and acetochlor pollution.